IMPROVING STUDENTS’ WRITING ABILITY BY USING SEQUENCE PICTURES AT X GRADE OF SMA KATOLIK ATMAJAYA TOLITOLI - Ismail Yunus H (Jurnal Madako Education, 2019)
This research design belongs to a pre-experimental research. The instruments of collecting data are pretest and posttest. The test was used to obtain data in order to find out the effect of using sequences pictures in writing procedure text.The result of the research shows that: 1. by using sequences pictures can improve students’ writing ability in procedure text, 2. there is significant difference between the result of pretest and posttest, the mean score of posttest was 78,40 it was higher than the mean score of pretest 56,0. 3. The testing hypothesis shows that Tcount 9,167was higher than Ttable 2,093. It indicates that the null hypothesis (Ho) rejected and the alternative hypothesis (Ha) accepted. Finally, this research shows that students’ ability was improved after they were taught using sequences pictures. They were better in their procedure text writing. It was signed by their improvements of writing component are organization, Vocabulary and grammar. Key Words: Sequence Pictures, Ability, Writing, Improving.